Morphological Interference of Muna Language Speakers in the Use of Indonesian Language - Darmin, Laode; Dian Danayanti Degeng, Putu; Junining, Esti (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl JanuaryDO - 10.24843/e-jl.2020.v14.i01.p12, 2020)
This study aims to examine the Muna language interference on the morphological aspects as a symptom of language that generally occurs in bilingual people. The influence of Muna language as a mother tongue and the difference between the morphological system of Muna and Indonesian is very possible for interference. This study was conducted with 20 participants from different community groups within the scope of Kecamatan Mawasangka, Kabupaten Buton Tengah. The data were collected using observation method with involved and uninvolved conversation, records and transcribing technique then analyzed using padan or Contrastive method to determine the presence of morphological interference. The result showed that Interference in the aspect of affixation in this research occurs in the formation of the prefix {ka-}, prefix {kafo-}, prefix {ta-}, and confix {ka-...-i}. whereas in the aspect of reduplication the interference symptoms are found in the form of partial reduplication of the Muna language morphological system.  Finally, the suggestion in this research that it is expected that the readers can have better understanding about interference and be more careful in using language. so as to reduce interference or distortion in language.